Ultradrawing and ultimate tensile properties of novel ultra-high molecular weight polyethylene composite fibers filled with nanoalumina fillers. Issue 16 (October 2016) - Yeh, Jen-taut; Wang, Chuen kai; Tsai, Chih-Chen; Ren, Dao-Huan; Chiu, Shih-Hsuan
Novel ultra-high molecular weight polyethylene (UHMWPE)/nanoalumina (F100 Ay ), UHMWPE/acid-treated nanoalumina (F100 Aox%-8-y ) and UHMWPE/functionalized nanoalumina (F100 Aox%-8 1 PEg-MAH x y ) as-prepared nanocomposite fibers were prepared by gel-spinning processes. The rod-like features of the original nanoalumina fillers were significantly etched into broken/shorter nanorods and/or shreds by oxalic acid solutions as their concentrations and/or treating time increased. As evidenced by Fourier transform infrared and transmission electron microscopy analysis, PEg-MAH molecules were successfully grafted onto acid-treated nanoalumina fillers through the reaction of the hydroxyl groups of nanoalumina fillers with the maleic anhydride groups of PEg-MAH molecules during their modification processes. The specific surface areas of each Aox%-8 1 PEg-MAH x y functionalized nanoalumina filler reached a maximum value (≧470 m 2 /g), as the weight ratios of PEg-MAH to acid-treated nanoalumina approached the optimal value at 8. The achievable draw ratio ( Dra ) values of F100 Ay, F100 Aox%-8-y and/or F100 Aox%-8 1 PEg-MAH x y as-prepared fibers approach a maximal value as the original, acid-treated and/or functionalized nanoalumina contents reach the optimal values at 0.1, 0.1 and 0.075 phr, respectively, in which, the maximal Dra values obtained for F100 Aox%-8 1 PEg-MAH x 0.075 as-prepared fiber specimens are significantly higher than those of the F100 A0.1 and F100 Aox%-8-0.1 drawn fiber specimens prepared at the same draw ratios. Moreover, the maximal Dra values obtained for F100 Aox%-8 1 PEg-MAH x 0.075 as-prepared fibers reached another maximal value as the functionalized nanoalumina fillers were modified using the optimal weight ratio of PEg-MAH to acid-treated nanoalumina at 8. Further investigation revealed that excellent orientation and tensile properties of the UHMWPE nanocomposite fibers can be obtained by ultradrawing the F100 Aox%-8 1 PEg-MAH x y as-prepared fibers with proper amounts of well-dispersed functionalized nanoalumina fillers.